Spatial structure and genetic diversity of natural populations of the Caribbean pine, Pinus caribaea var. bahamensis (Pinaceae), in the Bahaman archipelago. (12th February 2014) - Sanchez, Michele; Ingrouille, Martin J.; Cowan, Robyn S.; Hamilton, Martin A.; Fay, Michael F.
<x xml:space="preserve">Abstract</x> For the first time a comprehensive population genetics study of the endemic Caribbean pine, Pinus caribaea var. bahamensis, in the Bahamas and the Turks and Caicos Islands (TCI) is undertaken. Information on inbreeding levels, genetic diversity and spatial structure in the focus taxon are important tools for its future conservation and can help guide local forest management. Plastid (pDNA) and nuclear microsatellite (nDNA) loci were used to reveal past and contemporary patterns of genetic differentiation and levels of genetic diversity and to test the hypothesis of isolation by distance of populations in the Bahamas and TCI regions. Due to its non‐recombinant nature, low mutation rates and uniparental inheritance, pDNA can give an insight into an earlier state of the populations than that revealed by nDNA. Data from pDNA showed only 12 haplotypes, with one of them present in c. 81% of individuals, low unbiased genetic diversity (uh < 0.107) and lack of significant variation between regions (FCT = 0.011, P = 0.20); whereas nDNA showed higher unbiased genetic diversity (uHS > 0.487) and significant variation between regions (FCT = 0.156, P < 0.01). Isolation by distance was only significant for nDNA (r2 = 0.56, P < 0.01). Only two of the populations had significant levels of inbreeding (FIS = 0.090, FIS = 0.113). High levels of gene flow and lack of isolation in the past were revealed by pDNA, whereas nDNA showed a more recent spatial isolation and genetic differentiation between the Bahamas and TCI populations. Conservation measures are discussed in view of the genetic diversity, inbreeding and spatial structure found in the taxon. © 2014 The Linnean Society of London, Botanical Journal of the Linnean Society, 2014, 174, 359–383.